IN MEMORIAM: PROFESSOR LYDIA BAUMBACH - Schoeman, Marie (Akroterion, 2014)
The death of Lydia Baumbach in Groote Schuur Hospital on 9 February 1991 came as a shock to all who knew her, and especially to those who had heard her deliver a paper at the biennial conference of the Classical Association of South Africa at the University of Cape Town in January. She was in good spirits and to all appearances in good health, although we knew that she was going to see a specialist immediately after her paper to fix a date for an orthopedic operation.